Teacher-Parent Cooperation and Pupils’ Achievements in the Perception of Adult Respondents (Based on the Example of Secondary Schools) - Musiał, Ewa (Pedagogika, 2014)
The school’s main objective is to provide broad and comprehensive development of a pupil considering both educational (teaching) and protective aspects. Not only a pupil– teacher but also a parent-teacher vital cooperation is needed in order to achieve school’s goals and objectives. The dialogue between pupils, teachers and parents is indeed extremely important and should be kept going systematically throughout pupil’s education. Without the cooperation between teachers and parents, accordingly to the assumption: “We (teachers) teach-parents help, parents raise – we (teachers) help. Nothing about us, without us”, the effective school improvement cannot be realized. Ultimately, the communication between school and home is necessary to determine child’s best interests. The school-home cooperation and the increasing knowledge and awareness in this area is significantly important for the future analysis in carrying out educational researches.